Development of teaching materials based on learning video using movavi education set at Yayasan Perguruan Tunas Karya Batang Kuis - Jaya, Ivan; Nasution, Mahyuddin K. M. (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The COVID-19 pandemic that has recently hit various countries including Indonesia has resulted in major changes in various fields, including in the development of the education sector. The teaching and learning process has turned from face-to-face into an online method. However, there are several obstacles experienced by schools that implement an online learning system, one of them was the ability of teachers who do not understand various learning application platforms. In addition, the material provided by the teacher is not maximally acceptable to students because most teachers provide learning material from the pages of textbooks or teacher writings (scans, photos, or presentation files). For this reason, it is necessary to have variations in the provision of teaching materials to students by making interesting and creative learning videos using the Movavi Education Set. With learning videos, students can do lessons at home, repeat it, and can ask the teacher some points from it if they don't understand. By using Movavi Education Set, teachers are also free to be creative in making learning videos that can be shared through commonly used communication applications such as e-mail, WhatsApp, line, google classroom and other applications.